2018
DOI: 10.1534/g3.118.200627
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mutation in Brain Tumor Causes Both Neural Over-Proliferation and Neurodegeneration in AdultDrosophila

Abstract: A screen for neuroprotective genes in Drosophila melanogaster led to the identification of a mutation that causes extreme, progressive loss of adult brain neuropil in conjunction with massive brain overgrowth. We mapped the mutation to the brain tumor (brat) locus, which encodes a tripartite motif-NCL-1, HT2A, and LIN-41 (TRIM-NHL) RNA-binding protein with established roles limiting stem cell proliferation in developing brain and ovary. However, a neuroprotective role for brat in the adult Drosophila brain has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 96 publications
(117 reference statements)
0
12
0
Order By: Relevance
“…All these studies indicate that it is not miRNA alone, but the composition of miRISC has a great significance in the pathophysiology of disorders of the nervous system. There is Bhattacharyya, 2016, 2018) FMRP (Castren et al, 2005;Tervonen et al, 2009;Callan et al, 2010;Saffary and Xie, 2011;Jeon et al, 2014) TRIM-32 (Brat, mei-P26,NHL-2) (Bello, 2006;Betschinger et al, 2006;Lee et al, 2006;Bowman et al, 2008;Neumüller et al, 2008;Hammell et al, 2009;Schwamborn et al, 2009;Loewen et al, 2018) Hu Proteins (Marusich et al, 1994;Dobashi et al, 1998;Kasashima et al, 1999;Anderson et al, 2000;Akamatsu et al, 2002Akamatsu et al, , 2005Perrone-Bizzozero and Bolognani, 2002;Kraushar et al, 2014) Pumilio (Burow et al, 2015;Zahr et al, 2018) ESCRT Factors FMRP (Dockendorff et al, 2002;Ivanco and Greenough, 2002;Morales et al, 2002;Michel, 2004;Pan et al, 2004;Li, 2009;Doll and Broadie, 2015;Wang et al, 2015;Zimmer et al, 2017;Shen et al, 2019) MOV10 (Skariah et al, 2017) Pumilio (Menon et al, 2004(Menon et al, , 2009Ye et al, 2004;Vessey et al, 2010;...…”
Section: Discussionmentioning
confidence: 99%
“…All these studies indicate that it is not miRNA alone, but the composition of miRISC has a great significance in the pathophysiology of disorders of the nervous system. There is Bhattacharyya, 2016, 2018) FMRP (Castren et al, 2005;Tervonen et al, 2009;Callan et al, 2010;Saffary and Xie, 2011;Jeon et al, 2014) TRIM-32 (Brat, mei-P26,NHL-2) (Bello, 2006;Betschinger et al, 2006;Lee et al, 2006;Bowman et al, 2008;Neumüller et al, 2008;Hammell et al, 2009;Schwamborn et al, 2009;Loewen et al, 2018) Hu Proteins (Marusich et al, 1994;Dobashi et al, 1998;Kasashima et al, 1999;Anderson et al, 2000;Akamatsu et al, 2002Akamatsu et al, , 2005Perrone-Bizzozero and Bolognani, 2002;Kraushar et al, 2014) Pumilio (Burow et al, 2015;Zahr et al, 2018) ESCRT Factors FMRP (Dockendorff et al, 2002;Ivanco and Greenough, 2002;Morales et al, 2002;Michel, 2004;Pan et al, 2004;Li, 2009;Doll and Broadie, 2015;Wang et al, 2015;Zimmer et al, 2017;Shen et al, 2019) MOV10 (Skariah et al, 2017) Pumilio (Menon et al, 2004(Menon et al, , 2009Ye et al, 2004;Vessey et al, 2010;...…”
Section: Discussionmentioning
confidence: 99%
“…A novel genetic model for neurodegeneration recently was described in Drosophila [166] (Table 7). This model consists of a new mutation in the TRIM-NHL (tripartite motif-NCL-1, HT2A, and LIN-41) protein encoded by the Drosophila brain tumor (brat) gene.…”
Section: The Brain Tumor Gene and Neurodegenerationmentioning
confidence: 99%
“…[32][33][34]. Intriguingly, a recent study has suggested that the decision for INPs to differentiate or revert to NSC fate in certain brat mutants could be stochastic [35]. The majority of the proliferating cells in these tumours are not type II neuroblasts but are likely INPs that maintain the ability to self-renew and produce neurons and glia [35].…”
Section: Neural Lineages As the Source Of Tumoursmentioning
confidence: 99%